Internalizing Character Values in the Midst of the Toxic Communication Phenomenon in Adolescent Digital Interaction - Effiati Juliana Hasibuan; Nurrahmi Lasahido (Jurnal Ragam Pengabdian, 2026)
The phenomenon of toxic communication in adolescents' digital interactions, such as cyberbullying, hate speech, and covert verbal aggression is a serious challenge to strengthening character education in the digital era. This study aims to analyze the process of internalizing character values in the midst of the rampant toxic communication in adolescents in the peri-urban area of Deli Serdang Regency, North Sumatra, which borders the city of Medan. The research uses a qualitative approach with a case study design. Data were collected through in-depth interviews with 24 junior high and high school adolescents, 6 teachers, and 5 parents, complemented by digital interaction observation and targeted group discussions (FGD). The analysis was carried out using thematic analysis with stages of data reduction, categorization, and reflective interpretation. The results showed that toxic communication was normalized through a culture of sarcastic humor, peer pressure, and the reproduction of communication patterns from social media. However, the internalization of character values, including empathy, digital responsibility, respect, and self-control is formed through three main mechanisms: dialogical family mediation, school-based character education integration, and the practice of collective reflection between peers. Consistency of strengthening values in the family and school environment has been shown to increase critical awareness and the ability to regulate adolescents' emotions in responding to toxic communication. This research contributes to the development of the study of digital character education by placing the internalization of values as a social process influenced by the structure of relationships and local digital culture, as well as emphasizing the importance of a cross-environmental collaborative approach in building ethical and resilient digital citizenship.